Acute and Chronic Hyponatremia - Kheetan, Murad; Ogu, Iheanyichukwu; Shapiro, Joseph I.; Khitan, Zeid J. (Frontiers in Medicine, 2021)
Hyponatremia is the most common electrolyte disorder in clinical practice. Catastrophic complications can occur from severe acute hyponatremia and from inappropriate management of acute and chronic hyponatremia. It is essential to define the hypotonic state associated with hyponatremia in order to plan therapy. Understanding cerebral defense mechanisms to hyponatremia are key factors to its manifestations and classification and subsequently to its management. Hypotonic hyponatremia is differentiated on the basis of urine osmolality, urine electrolytes and volume status and its treatment is decided based on chronicity and the presence or absence of central nervous (CNS) symptoms. Proper knowledge of sodium and water homeostasis is essential in individualizing therapeutic plans and avoid iatrogenic complications while managing this disorder.